Role of Leaders’ Emotional Labor toward Leader’s Job Satisfaction and Emotional Exhaustion: Moderating Role of Psychological Capital - Sania Noreen; Qasim Ali Nisar; Shahbaz Haider; Tan Fee Yean (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2021)
Everyone has to manage the emotions during their interaction with others; similar case is with the leaders in organizations. Leaders’ actively and continually regulate their emotional state. The crucial role of emotions in interactional process as well in decision making triggers leaders to be vigilant about their emotional labor strategies. Thus emotional labor has become an emerging construct in leadership domain. This study has collected data from 250 doctors working in private and public hospitals in Gujranwala. Findings demonstrated leaders’ deep acting as well as displaying natural emotions are positively associated with job satisfaction and negatively associated with leaders’ emotional exhaustion. Moreover, surface acting has significant positive relationship with leaders’ emotional exhaustion and negative relationship with leaders’ job satisfaction. Psychological capital significantly moderated the relationship between leaders’ emotional labor strategies, leaders’ job satisfaction and leaders’ emotional exhaustion.